Creative origami & beyond : inspiring tips, techniques, and projects for transforming paper into folded works of art /: inspiring tips, techniques, and projects for transforming paper into folded works of art. (2016) - Chan, Jenny W; Frasco, Paul; Sato, Coco; Tamaki, Stacie
No abstract available